UTILIZATION OF ENVIRONMENTAL MEDIA TO IMPROVE CHILDREN'S STORYLING ABILITY IN STUDENTS GROUP A AL FURQON MAESAN BONDOWOSO - supatmi hendra watiningsih (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
This study aims to improve the storytelling ability of children in group A of Al Furqon Maesan Bondowoso Kindergarten students in the odd semester of the 2020/2021 academic year. Before the action was given, the children's storytelling ability in group A and the teacher sought alternative solutions by using several methods and media in learning. The application of the media has not been able to improve the storytelling ability of children in group A. The solution offered in this study is to use environmental media in storytelling learning. The research subjects included all 33 students in group A, and teachers in group A. Data collection techniques used observation and interview methods. Interview sheets and observation sheets aim to find out how teachers use environmental media to improve children's storytelling skills in Al Furqon Maesan Bondowoso Kindergarten students and are expected to be used as guidelines or provisions for me as a teacher in the teaching and learning process, as well as improve and direct students to always speak fluently. The procedure in this study has four stages, namely planning, implementation, observation, and reflection. The performance indicators in this classroom action research are, it is hoped that using environmental media to improve children's storytelling skills in group A of AL Furqon Maesan Bondowoso Kindergarten students in the odd semester of the 2020/2021 academic year can improve children's storytelling skills which are shown to increase children's storytelling abilities above the Minimum Mastery Criteria (KKM), minimum 80% of 33 students. The results of this study indicate that before the action of using environmental media in storytelling learning as many as 8 children (36.4%). After the agreed action was taken, namely by using environmental media in the first cycle, the children's storytelling ability increased to 18 children (54.5%), and in the second cycle increased to 29 children (87%). Based on the results of data analysis in this action research, the hypothesis states It is suspected that using environmental media can improve the storytelling ability of children in group A of Al Furqon Maesan Bondowoso Kindergarten students in the odd semester of the 2020/2021 academic year, which is proven and acceptable